Food processing : (Blackwell, 2004)
Renowned international academicians and food industry professionals have collaborated to create Food Processing: Principles and Applications. This practical, fully illustrated resource examines the principles of food processing and demonstrates their application by describing the stages and operations for manufacturing different categories of basic food products.